Synthesis of the polyketide section of seragamide A and related cyclodepsipeptides via Negishi cross coupling - Lang, Jan Hendrik; Lindel, Thomas (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of the polyketide section present in the potently cytotoxic marine cyclodepsipeptide jasplakinolide and related natural products, geodiamolides and seragamides, is reported. The key step is a Negishi cross coupling of (R)-(3-methoxy-2-methyl-3-oxopropyl)zinc(II) bromide and an (E)-iodoalkene that was synthesized via an aluminium ester enolate attack at (R)-propylene oxide. The overall synthesis comprises nine steps with an overall yield of 21%. It proved to be possible to liberate the free 8-hydroxynonenoic acid and to couple it with a protected tripeptide composed of L-alanine, N,O-dimethyl-D-iodotyrosine, and TIPS-protected L-threonine, which occurs as partial structure of seragamide A. The tripeptide section of seragamide A was assembled by solution-phase synthesis and an open-chain analogue of the natural product was obtained.
Keywords: jasplakinolide; marine natural products; Negishi coupling; polyketides; stereoselective synthesis

(untitled) - Crews, P.; Manes, L. V.; Boehler, M. (Tetrahedron Lett., 1986)

(untitled) - Zabriskie, T. M.; Klocke, J. A.; Ireland, C. M.; Marcus, A. H.; Molinski, T. F.; Faulkner, D. J.; Xu, C.; Clardy, J. C. (J. Am. Chem. Soc., 1986)

(untitled) - Pospich, S.; Kumpula, E.-P.; von der Ecken, J.; Vahokoski, J.; Kursula, I.; Raunser, S. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Chan, W. R.; Tinto, W. F.; Manchand, P. S.; Todaro, L. J. (J. Org. Chem., 1987)

(untitled) - Coleman, J. E.; Van Soest, R.; Andersen, R. J. (J. Nat. Prod., 1999)
And references cited therein.

(untitled) - Tanaka, C.; Tanaka, J.; Bolland, R. F.; Marriott, G.; Higa, T. (Tetrahedron, 2006)

(untitled) - Wartmann, T.; Lindel, T. (Eur. J. Org. Chem., 2013)

(untitled) - Schäckermann, J.-N.; Lindel, T. (Z. Naturforsch., B: J. Chem. Sci., 2014)

(untitled) - Arndt, H.-D.; Rizzo, S.; Nöcker, C.; Wakchaure, V. N.; Milroy, L.-G.; Bieker, V.; Calderon, A.; Tran, T. T. N.; Brand, S.; Dehmelt, L.; Waldmann, H. (Chem. – Eur. J., 2015)

(untitled) - Rao, A. V. R.; Gurjar, M. K.; Nallaganchu, B. R.; Bhandari, A. (Tetrahedron Lett., 1993)

(untitled) - Grieco, P. A.; Hon, Y. S.; Perez-Medrano, A. (J. Am. Chem. Soc., 1988)

(untitled) - Chu, K. S.; Negrete, G. R.; Konopelski, J. P. (J. Org. Chem., 1991)

(untitled) - Ghosh, A. K.; Moon, D. K. (Org. Lett., 2007)

(untitled) - Hirai, Y.; Yokota, K.; Sakai, H.; Yamazaki, T.; Momose, T. (Heterocycles, 1989)

(untitled) - White, J. D.; Amedio, J. C., Jr (J. Org. Chem., 1989)

(untitled) - Schmidt, U.; Siegel, W.; Mundinger, K. (Tetrahedron Lett., 1988)

(untitled) - Rao, A. V. R.; Gurjar, M. K.; Nallaganchu, B. R.; Bhandari, A. (Tetrahedron Lett., 1993)

(untitled) - Imaeda, T.; Hamada, Y.; Shioiri, T. (Tetrahedron Lett., 1994)

(untitled) - Kang, S.-K.; Lee, D.-H. (Synlett, 1991)

(untitled) - Wattanasereekul, S.; Maier, M. E. (Adv. Synth. Catal., 2004)

(untitled) - Tannert, R.; Hu, T.-S.; Arndt, H.-D.; Waldmann, H. (Chem. Commun., 2009)

(untitled) - Tannert, R.; Milroy, L.-G.; Ellinger, B.; Hu, T.-S.; Arndt, H.-D.; Waldmann, H. (J. Am. Chem. Soc., 2010)

(untitled) - Ashworth, P.; Broadbelt, B.; Jankowski, P.; Kocienski, P.; Pimm, A.; Bell, R. (Synthesis, 1995)

(untitled) - Unsworth, P. J.; Leonori, D.; Aggarwal, V. K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Gorges, J.; Kazmaier, U. (Org. Lett., 2018)

(untitled) - Eggert, U.; Diestel, R.; Sasse, F.; Jansen, R.; Kunze, B.; Kalesse, M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Waldmann, H.; Hu, T.-S.; Renner, S.; Menninger, S.; Tannert, R.; Oda, T.; Arndt, H.-D. (Angew. Chem., Int. Ed., 2008)

(untitled) - Schmauder, A.; Sibley, L. D.; Maier, M. E. (Chem. – Eur. J., 2010)

(untitled) - Becker, D.; Kazmaier, U. (Eur. J. Org. Chem., 2015)

(untitled) - Petri, A. F.; Schneekloth, J. S.; Mandal, A. K.; Crews, C. M. (Org. Lett., 2007)

(untitled) - Cui, C.; Dai, W.-M. (Org. Lett., 2018)

(untitled) - Dimopoulos, P.; Athlan, A.; Manaviazar, S.; Hale, K. J. (Org. Lett., 2005)

(untitled) - Francavilla, C.; Chen, W.; Kinder, F. R., Jr (Org. Lett., 2003)

(untitled) - Corrêa, I. R.; Pilli, R. A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Sturm, T.-J.; Marolewski, A. E.; Rezenka, D. S.; Taylor, S. K. (J. Org. Chem., 1989)

(untitled) - Taylor, S. K.; Fried, J. A.; Grassl, Y. N.; Marolewski, A. E.; Pelton, E. A.; Poel, T.-J.; Rezanka, D. S.; Whittaker, M. R. (J. Org. Chem., 1993)

(untitled) - Qabaja, G.; Benavides, A. R.; Liu, S.; Petersen, K. S. (J. Org. Chem., 2015)

(untitled) - Hagiya, K.; Muramoto, N.; Misaki, T.; Sugimura, T. (Tetrahedron, 2009)

(untitled) - Handa, M.; Scheidt, K. A.; Bossart, M.; Zheng, N.; Roush, W. R. (J. Org. Chem., 2008)

(untitled) - Roth, G. J.; Liepold, B.; Müller, S. G.; Bestmann, H. J. (Synthesis, 2004)

(untitled) - Sengoku, T.; Uemura, D.; Arimoto, H. (Chem. Lett., 2007)

(untitled) - Klement, I.; Knochel, P.; Chau, K.; Cahiez, G. (Tetrahedron Lett., 1994)

(untitled) - Pitt-Rivers, R. (Chem. Ind., 1956)

(untitled) - Edgar, K. J.; Falling, S. N. (J. Org. Chem., 1990)

(untitled) - Schmidt, E. W.; Nelson, J. T.; Fillmore, J. P. (Tetrahedron Lett., 2004)

(untitled) - Das, B.; Krishnaiah, M.; Venkateswarlu, K.; Reddy, V. S. (Tetrahedron Lett., 2007)

(untitled) - Hitotsuyanagi, Y.; Miyazawa, A.; Hinosawa, T.-a.; Nakagawa, Y.; Hasuda, T.; Takeya, K. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Moschitto, M. J.; Lewis, C. A. (Eur. J. Org. Chem., 2016)

(untitled) - Katsuyama, A.; Yakushiji, F.; Ichikawa, S. (J. Org. Chem., 2018)